2008
DOI: 10.1161/circresaha.108.183327
|View full text |Cite|
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor and Semaphorin Induce Neuropilin-1 Endocytosis via Separate Pathways

Abstract: Abstract-The neuropilin (Nrp)1 receptor is essential for both nervous and vascular system development. Nrp1 is unusually versatile, because it transmits both chemoattractive and repulsive signals in response to vascular endothelial growth factor (VEGF)-A and class 3 semaphorins, respectively. Both Nrp1 and VEGF receptor 2 undergo ligand-dependent endocytosis. We sought to establish the endocytic pathway of Nrp1 and to determine whether uptake is required for its signaling. Whereas Nrp1 underwent clathrin-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 42 publications
(63 reference statements)
8
99
0
1
Order By: Relevance
“…However, the two mAb-A22p antibodies exhibited similarly enhanced levels (approximately 1.5-fold) of tumor tissue penetration compared with the parent mAbs ( Although Fc-A22p acted as an agonist of NRPs triggering its cellular internalization and exerting the biologic activities, the monovalent A22p peptide did not even at 100 mmol/L, suggesting that the bivalent engagement of NRP1/2 by Fc-/mAb-A22p is essential for effective NRPmediated signaling. Therefore, fusion of the NRP-targeting A22p to the heavy chain C-terminus of mAb seems to induce receptor dimerization by binding to the argininebinding pocket in the b1 domain of NRP1/2, mimicking the homodimeric binding of VEGF or Sema3 ligands to NRPs (15,33). VEGF-and Sema3A-induced vascular permeability is commonly dependent on NRP1 coreceptor, but also requires the signal transducing receptor of VEGF-R2 and plexin, respectively (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the two mAb-A22p antibodies exhibited similarly enhanced levels (approximately 1.5-fold) of tumor tissue penetration compared with the parent mAbs ( Although Fc-A22p acted as an agonist of NRPs triggering its cellular internalization and exerting the biologic activities, the monovalent A22p peptide did not even at 100 mmol/L, suggesting that the bivalent engagement of NRP1/2 by Fc-/mAb-A22p is essential for effective NRPmediated signaling. Therefore, fusion of the NRP-targeting A22p to the heavy chain C-terminus of mAb seems to induce receptor dimerization by binding to the argininebinding pocket in the b1 domain of NRP1/2, mimicking the homodimeric binding of VEGF or Sema3 ligands to NRPs (15,33). VEGF-and Sema3A-induced vascular permeability is commonly dependent on NRP1 coreceptor, but also requires the signal transducing receptor of VEGF-R2 and plexin, respectively (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular internalization of NRP1/2 in response to their intrinsic ligands, such as VEGF165 and Sema3A, is essential for triggering intracellular signaling (14,33). When FcA22p was incubated at 37 C for 30 minutes with HUVECs and SK-OV-3 tumor cells, it was internalized into the cells and colocalized with NRP1 and NRP2 as well as the early endosomal marker EEA1 ( Fig.…”
Section: Fc-a22p Specifically Interacts With Nrps Undergoing Cellularmentioning
confidence: 95%
“…Thus, intriguing new data suggest that the cytoplasmic NRP1 domain binds the protein GIPC (also known as synectin) to link neuropilin-containing vesicles to the transport machinery via myosin 6. 58 This pathway may control the intracellular distribution of at least two NRP1 co-receptors, VEGFR2 and PLXND1, 31,59 but it additionally provides an interface to integrins. 60 The idea that neuropilins control the function not only of L1-CAM, but also integrins has brought us full circle to the original discovery of neuropilin as an adhesion molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been suggested that NRP1 enhances the affinity of VEGF165 for VEGFR2, 29 and that it enhances VEGF165 signaling by promoting VEGFR2 clustering 30 or VEGFR2 endocytosis. 31 Alternatively, or additionally, NRP1 may act on endothelium from a non-endothelial cell type in trans, as described for tumour cells 30 and haematopoietic cells. 32 In most cases, NRP1 has been implicated in enhancing VEGFstimulated cell migration, rather than to phenocopy the defect caused by loss of SEMA3F.…”
Section: Vegf Isoforms In Neuropilin-mediated Cell Migrationmentioning
confidence: 99%
“…Binding of VEGF to extracellular domain of VEGFR2 triggers internalization of receptor subsequent to its dimerization and phosphorylation at TYR1054 and TYR1059. Upon activation, VEGFR2 dissociates from caveolin and transported to endosomes (Salikhova et al, 2008). Multiple modes of VEGFR2 internalization exist, since VEGF-stimulated endocytosis of VEGFR2 is clathrin-dependent (Lampugnani et al, 2006), and VEGFR2 is known to be translocated to perinuclear caveosomes through caveolar endocytosis (Bauer et al, 2005;Labrecque et al, 2003).…”
Section: Endocytic Trafficking Of Vegfr2mentioning
confidence: 99%